Viscosity modified material for synchronous grouting of seabed shield tunnel as well as preparation method and use method of viscosity modified material

By adding viscosity modified materials to simultaneous grouting materials, the problems of poor construction performance, large shrinkage after hardening, difficulty in filling gaps, difficulty in resisting seawater erosion and poor durability are solved, achieving efficient construction performance improvement and durability enhancement. .

CN119349922APending Publication Date: 2025-01-24CHINA RAILWAY TUNNEL GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411532312.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing synchronous grouting materials have problems such as poor construction performance, large shrinkage after hardening, difficulty in effectively filling the voids behind the wall, difficulty in resisting seawater erosion and poor durability in the construction of subsea shield tunnels.

Method used

A viscosity modified material is used. The raw materials include dispersant, underwater anti-dispersion agent, tackifier, rubber powder and defoaming agent. It is prepared by direct mixing and stirring, and is used in conjunction with the simultaneous grouting slurry in a certain proportion.

Benefits of technology

It has greatly improved the construction and easyness of synchronous grouting, reducing the separation and water secretion of the slurry in the construction. The intensity of the pulp after hardening and almost no shrinkage. Durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110730930000061
    Figure BDA0005110730930000061
Patent Text Reader

Abstract

The invention discloses a viscosity modified material for synchronous grouting of seabed shield tunnels, raw materials comprise a dispersing agent, an underwater anti-dispersing agent, a tackifier, rubber powder and a defoaming agent, the dispersing agent is cement or lime, and the underwater anti-dispersing agent is a netted polymer organic compound which chemically reacts with a cementing material; the construction workability and grout performance of synchronous grouting can be greatly improved, segregation and bleeding phenomena of grout in construction are reduced, hardened grout is high in strength and almost free of shrinkage, gaps behind a wall can be effectively filled, synchronous grouting can timely stabilize segments, the construction progress is accelerated, the construction efficiency is greatly improved, and the construction cost is reduced. Meanwhile, the use amount of cement, fly ash and other cementing materials is saved, and the construction cost is saved. A synchronous grouting viscosity modified material is used, the seawater corrosion resistance of the synchronous grouting material can be greatly improved, a dry-wet cycle accelerated damage test is adopted in a 5% sodium sulfate solution, and after the synchronous grouting material is soaked for 56 days, the mass loss rate is smaller than 5%; the strength reduction rate is less than 3%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a synchronous grouting additive, and in particular to a viscosity-modified material for synchronous grouting of a submarine shield tunnel, a preparation method and a use method thereof. Background Art

[0002] In the construction of large-diameter shield tunnels on the seabed or riverbed, the floating of the pipe segments has become an important issue affecting the quality control of shield construction. At present, the synchronous grouting of shields in China is mainly based on cement (adding fly ash) mortar. This type of slurry has a long setting time and good fluidity. However, if the quality control is not good, it often causes a low slurry stone rate and poor dilution resistance. It is easy to be diluted in the strata rich in groundwater and cannot be solidified for a long time. Moreover, the shrinkage rate after consolidation is large, and there is a large gap behind the pipe segment wall. The buoyancy of the pipe segment after it escapes from the shield tail is related to the volume of the water discharged. This type of slurry is difficult to provide shear resistance after being diluted. Not only can it not resist the floating of the pipe segment, it even increases the water content in the stratum, which is more likely to cause the pipe segment to float, thus causing a series of quality problems such as misalignment, cracking, and water seepage. Synchronous grouting plays an important role in controlling the floating of the pipe segment, improving the assembly quality of the pipe segment, timely stabilizing the pipe segment, and accelerating the construction progress. Synchronous grouting has become an important factor affecting the quality control of shield construction. However, due to the relatively few control indicators for the quality of synchronous grouting in various industry specifications, there is no basis for the design of slurry mix ratio, and there is no unified standard for slurry quality testing. The quality of synchronous grouting of various construction units is uneven, which brings great safety and quality risks to shield construction. In particular, in the investigation of the slurry mix ratio commonly used in engineering, it is found that the raw materials are traditional and single, the water consumption is large, and the slurry is very easy to produce segregation and slurry. Therefore, it is necessary to add admixtures in a targeted manner to improve the slurry performance of synchronous grouting. The admixtures used in the existing synchronous grouting slurry ratio are few in variety and single in function, which cannot effectively improve the quality of synchronous grouting and are difficult to adapt to the construction characteristics of synchronous grouting. In particular, the slurry is easy to segregate and precipitate, and the setting time is difficult to control; and the shrinkage rate of the slurry is large after hardening, resulting in a large gap behind the wall of the pipe segment. In addition, synchronous grouting is mostly mixed on site. Due to the limitations of the construction site and production conditions, the raw materials used for synchronous grouting are relatively simple, and often only conventional materials (such as cement, sand, bentonite, etc.) are used, which makes it difficult to ensure that synchronous grouting has good construction and workability. Synchronous grouting is prone to precipitation, segregation, and pipe blockage during construction. If only conventional materials are used, it is difficult to achieve the water-resistant dispersion performance and seawater erosion resistance of synchronous grouting materials. In coastal river-crossing tunnels, synchronous grouting is an important material for stabilizing pipe segments and filling gaps behind walls. Its long-term resistance to seawater erosion has not been effectively solved.

[0003] Therefore, it is necessary to solve the technical problems existing in the use of conventional synchronous grouting materials, such as poor construction performance, large shrinkage after hardening, difficulty in effectively filling the gaps behind the wall, difficulty in resisting seawater erosion, and poor durability. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a viscosity-modified material, a preparation method and a use method thereof for synchronous grouting of submarine shield tunnels, so as to solve the technical problems existing in conventional synchronous grouting materials, such as poor construction performance, large shrinkage after hardening, difficulty in effectively filling the voids behind the wall, difficulty in resisting seawater erosion, and poor durability.

[0005] The viscosity-modifying material for synchronous grouting of submarine shield tunnels of the present invention comprises the following components by weight: 4-10 parts of dispersant, 1-5 parts of underwater anti-dispersant, 2-6 parts of viscosity enhancer, 2-4 parts of rubber powder, and 0.5-1 part of defoamer, wherein the dispersant is cement or lime, and the underwater anti-dispersant is a network polymer organic compound that chemically reacts with the cementitious material;

[0006] Further, the underwater anti-dispersant is an organic polymer flocculant;

[0007] Furthermore, the viscosity increasing agent is one or both of hydroxypropyl methylcellulose HPMC and hydroxyethyl cellulose HEC;

[0008] Furthermore, the defoamer is one or a mixture of two or more of silicone, polyether, and polyether-modified polysiloxane defoamers;

[0009] Furthermore, the raw materials include the following components by weight: 7 parts of dispersant, 3 parts of underwater anti-dispersant, 4 parts of viscosity enhancer, 3 parts of rubber powder, and 0.8 parts of defoaming agent.

[0010] The invention also discloses a method for preparing a viscosity-modifying material for synchronous grouting of a submarine shield tunnel, wherein the raw materials are directly mixed and stirred to obtain the viscosity-modifying material.

[0011] The invention also discloses a method for using the viscosity modifying material for synchronous grouting of a submarine shield tunnel, wherein the viscosity modifying material and synchronous grouting slurry are used in a mass ratio of 1:60 to 1:90.

[0012] Beneficial effects of the present invention: The viscosity-modifying material, preparation method and use method for synchronous grouting of submarine shield tunnels of the present invention can greatly improve the construction and workability of synchronous grouting and the performance of slurry, reduce the segregation and bleeding of slurry during construction, and improve the strength of the slurry after hardening. The slurry has almost no shrinkage and can effectively fill the gaps behind the wall, so that the synchronous grouting can stabilize the pipe segments in time, speed up the construction progress, and greatly improve the construction efficiency. At the same time, it saves the amount of cement, fly ash and other cementitious materials, and saves construction costs. The use of the viscosity-modifying material for synchronous grouting can greatly improve the ability of the synchronous grouting material to resist seawater erosion. In a 5% sodium sulfate solution, a dry-wet cycle accelerated destruction test is adopted. After immersion for 56 days, the mass loss rate is less than 5%; the strength reduction rate is less than 3%. DETAILED DESCRIPTION

[0013] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0014] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0015] The viscosity modifier used for synchronous grouting of submarine shield tunnels in this embodiment includes the following components by weight: 4-10 parts of dispersant, 1-5 parts of underwater anti-dispersant, 2-6 parts of thickener, 2-4 parts of rubber powder, and 0.5-1 parts of defoamer. The dispersant is cement or lime, and the underwater anti-dispersant is a reticular polymer organic compound that reacts chemically with the cementitious material; the viscosity modifier is added to the synchronous grouting material as an external additive. The cement used is preferably ferroaluminate cement. The hydrate composition of sulfoaluminate cement and silicate cement is significantly different. The main component of the former is Aft (calcium sulfate), which gives this type of cement fast hardening, high strength and better antifreeze, anti-seepage and anti-corrosion properties. The hydrate liquid phase pH value of ferroaluminate cement is relatively high, which is 12.0-12.5, and can produce a passivation film on the surface of the steel bars in concrete. The anodic curve confirms that a passivation film is formed soon after the cement is hydrated, indicating that ferroaluminate cement will not cause steel bars to rust. Also, due to the high pH value of cement hydrate, a high alkalinity CSH (II) is formed, and the setting time of the synchronous grouting material can be adjusted. At the same time, the excellent seawater corrosion resistance of ferroaluminate cement also greatly improves the durability of the synchronous grouting material. The lime is slaked lime powder with a particle size of 200-300 mesh. The content of Ca0+Mg0 in the slaked lime is >90%, and the content of sulfur trioxide is <2%. It plays the role of dispersing rubber powder, anti-water dispersant, HPMC, and HEC. At the same time, the stone powder has good water absorption, increases the lubricity of the slurry, and improves the pumping performance of the slurry. The role of the underwater anti-dispersant is to react chemically with the cementitious material, so that the slurry has the effect of not dispersing in water, enhances the stability of synchronous grouting in water-rich strata, and prevents excessive dilution from causing the loss of cementitious materials and reducing strength; most submarine tunnels are in water-rich strata that are severely damaged by salt crystallization. The cohesiveness and anti-water dispersibility of the slurry are crucial to ensure the grouting effect. The viscosity enhancer is used to improve the cohesiveness and water retention of the slurry. With good water retention, it can also improve the pumpability of the synchronous grouting construction, and prevent and reduce pipe blockage during construction. Glue powder is a pale yellow to white dry powder that can be dissolved into a transparent colloid in tap water at room temperature. It is widely used in a variety of building coatings and modified premixed mortars based on mineral cementitious materials, such as water-resistant putty, porcelain paste, cement-based, lime-based, gypsum-based additives, etc. It does not contain organic volatiles and heavy metals such as formaldehyde, xylene, mercury, lead, etc., and is non-toxic to the human body. Use glue powder to improve the cohesiveness of the slurry and greatly improve the slurry's ability to resist segregation in water. Use defoaming components to reduce the excessive bubbles introduced by the use of anti-water dispersants.

[0016] In this embodiment, the underwater anti-dispersant is an organic polymer flocculant; the main component is a flocculant-like substance, and organic polymer flocculants are commonly used. Anionic ones include: polymers such as polyacrylic acid, sodium polyacrylate, calcium polyacrylate, and alkaline hydrolyzates of polyacrylamide, as well as copolymers such as styrene sulfonate, wood sulfonate, acrylic acid, and methacrylic acid; cationic ones include polyacrylamide flocculants, and some composite flocculants. Anti-dispersants are mainly reticular polymer organic compounds with high specific surface area, which can greatly increase the cohesiveness of the slurry and achieve good anti-dispersion effects through flocculation and bridging. But at the same time, a large number of tiny bubbles will be wrapped in, which is also the main reason why the slurry appears very soft. If the amount added is too large, the coagulation time will be affected and the strength will also be reduced. Under normal circumstances, it should be appropriate to ensure that there is a non-dispersing effect, and no excessive bubbles will be introduced, and the bulk density and strength will be reduced. Because the amount of anti-dispersant added is very small, in order to make the anti-dispersant evenly added to the slurry, cement is used as a dispersant.

[0017] In this embodiment, the viscosity increasing agent is one or both of hydroxypropyl methylcellulose HPMC and hydroxyethyl cellulose HEC; HPMC and HEC both have good thickening, suspension, dispersion, emulsification, adhesion, film-forming, moisture protection and protective colloid properties. Experiments have shown that the combination of the two materials can more easily improve the stability of the slurry.

[0018] In this embodiment, the defoamer is one or a mixture of two or more of the silicone, polyether, and polyether-modified polysiloxane defoamers; the defoamer cooperates with the underwater anti-dispersant: because the underwater anti-dispersant is mainly a network of high-molecular organic compounds with a high specific surface area, it can greatly increase the cohesiveness of the slurry, and achieve a good anti-dispersion effect through flocculation and bridging. But at the same time, a large number of tiny bubbles will be wrapped in, which is also the main reason why the slurry appears very soft. If the amount added is too large, it will affect the coagulation time and reduce the strength. Under normal circumstances, it should be appropriate to ensure that there is a non-dispersion effect without introducing excessive bubbles, reducing the bulk density and strength. At the same time, in order to control the bulk density of synchronous grouting and not reduce the strength of synchronous grouting after hardening, a defoamer is added to the composite viscosity-modifying material to reduce the inclusion of too many bubbles.

[0019] A preferred embodiment is that the raw materials include the following components by weight: 7 parts of dispersant, 3 parts of underwater anti-dispersant, 4 parts of viscosity enhancer, 3 parts of rubber powder, and 0.8 parts of defoaming agent. The viscosity modifying material of this embodiment has a better effect.

[0020] This embodiment also discloses a method for preparing a viscosity-modifying material for synchronous grouting of a submarine shield tunnel, wherein the raw materials are directly mixed and stirred to obtain the viscosity-modifying material.

[0021] This embodiment also discloses a method for using a viscosity modifying material for synchronous grouting of a submarine shield tunnel. The viscosity modifying material and synchronous grouting slurry are used in a mass ratio of 1:60 to 1:90. Generally, 20-30 kg is added to 1 cubic meter of synchronous grouting slurry, and the amount is adjusted according to the use effect.

[0022] Embodiment 1

[0023] The viscosity-modifying material for synchronous grouting of submarine shield tunnels in this embodiment comprises the following components by weight: 7 parts of cement, 5 parts of lime, 1.5 parts of underwater anti-dispersant (polyacrylic acid), 2 parts of HPMC, 1 part of HEC, 3 parts of rubber powder, and 0.5 parts of silicone defoaming agent.

[0024] Embodiment 2

[0025] The viscosity modifying material for synchronous grouting of submarine shield tunnels in this embodiment includes the following components by weight: 9 parts of cement, 3 parts of lime, 2.5 parts of underwater anti-dispersant (sodium polyacrylate), 1 part of HPMC, 2 parts of HEC, 2 parts of rubber powder, and 0.5 parts of polyether defoaming agent.

[0026] Embodiment 3

[0027] The viscosity modifying material for synchronous grouting of submarine shield tunnels in this embodiment includes the following components by weight: 10 parts of cement, 2 parts of lime, 3.5 parts of underwater anti-dispersant (calcium polyacrylate), 2 parts of HPMC, 1 part of HEC, 1 part of rubber powder, and 0.5 parts of polyether-modified polysiloxane defoaming agent.

[0028] Embodiment 4

[0029] The viscosity modifying material for synchronous grouting of submarine shield tunnels in this embodiment includes the following components by weight: 8 parts of cement, 4 parts of lime, 2.5 parts of underwater anti-dispersant (styrene sulfonate), 1 part of HPMC, 1.5 parts of HEC, 2.2 parts of rubber powder, and 0.8 parts of polyether-modified polysiloxane defoaming agent.

[0030] Embodiment 5

[0031] The viscosity modifying material for synchronous grouting of submarine shield tunnels in this embodiment includes the following components by weight: 8 parts of cement, 4 parts of lime, 4 parts of underwater anti-dispersant (lignosulfonate), 1 part of HPMC, 1.5 parts of HEC, 0.7 parts of rubber powder, and 0.8 parts of polyether defoamer.

[0032] Embodiment 6

[0033] The viscosity-modifying material for synchronous grouting of submarine shield tunnels in this embodiment includes the following components in parts by weight: 9 parts of cement, 3 parts of lime, 3 parts of underwater anti-dispersant (acrylic acid), 1 part of HPMC, 1.5 parts of HEC, 1.7 parts of rubber powder, and 0.8 parts of silicone defoaming agent.

[0034] The viscosity-modified material of Example 1 is used for synchronous grouting, and the effect is as follows:

[0035]

[0036] The effects of the viscosity-modified materials of Examples 2-6 of the present invention for synchronous grouting are better than those of Example 1.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A viscosity-modifying material for synchronous grouting of submarine shield tunnels, characterized in that: The raw materials include the following components by weight: 4-10 parts of dispersant, 1-5 parts of underwater anti-dispersant, 2-6 parts of viscosity enhancer, 2-4 parts of rubber powder, and 0.5-1 part of defoamer. The dispersant is cement or lime, and the underwater anti-dispersant is a network polymer organic compound that chemically reacts with the cementitious material.

2. The viscosity-modifying material for synchronous grouting of submarine shield tunnels according to claim 1, characterized in that: The underwater anti-dispersant is an organic polymer flocculant.

3. The viscosity-modifying material for synchronous grouting of submarine shield tunnels according to claim 1, characterized in that: The viscosity enhancer is one or both of hydroxypropyl methylcellulose HPMC and hydroxyethyl cellulose HEC.

4. The viscosity-modifying material for synchronous grouting of submarine shield tunnels according to claim 1, characterized in that: The defoaming agent is one or a mixture of two or more of silicone, polyether, and polyether-modified polysiloxane defoaming agents.

5. The viscosity-modifying material for synchronous grouting of submarine shield tunnels according to claim 1, characterized in that: The raw materials include the following components by weight: 7 parts of dispersant, 3 parts of underwater anti-dispersant, 4 parts of viscosity enhancer, 3 parts of rubber powder, and 0.8 parts of defoamer.

6. The method for preparing a viscosity-modifying material for synchronous grouting of a submarine shield tunnel according to claim 1, characterized in that: The raw materials are directly mixed and stirred to obtain the viscosity-modified material.

7. The method for using the viscosity-modifying material for synchronous grouting of a submarine shield tunnel according to claim 1, characterized in that: The viscosity modifying material and the synchronous grouting slurry are used in a mass ratio of 1:60 to 1:90.